Effect of Toxoplasma Infection Dosage on IgG, IgM, Fetus Weight and Body Length, and Necrosis of Placenta and Fetal Heart - Nurinasari, Hafi; Sajidan; Purwanto, Bambang; Indarto, Dono; Subekti, Didik T (Bogor Agricultural University, Indonesia, 2024)
One of the most prevalent zoonotic illnesses in the world, toxoplasmosis, affects both humans and animals and is caused by the parasite Toxoplasma gondii. The infection will trigger the immune system to increase antibody production. This study aims to determine the dose of toxoplasma that causes necrosis in rats placental and fetal hearts. This study was laboratory experimental research with a Randomized Control Trial (RCT). The study design used a post-test only with a control group design. The Ig G variable obtained from the control group (CG) and treatment group 3 (TG3) is the most significant because the mean value difference was the largest (176.56). The Ig M variable obtained from the control group with treatment group 3 (TG3) is the most significant because the mean value difference is the largest (33.47). The fetus weight variable obtained from the control group with treatment group 3 (TG3) is the most significant because the mean value difference is the largest (2.6). The body length variable obtained from the control group between treatment group 3 (TG3) is the most significant because the mean value difference is the largest (1.26). There was a significant difference in placental tissue necrosis (p = 0.034) and heart (p = 0.025) between the control group (CG) and treatment group 3 (TG3). Therefore, there was a significant difference in Ig G, Ig M, fetus weight, body length, placental tissue necrosis, and fetal heart at the 10³ dose compared to the 102, 101, and normal doses.